NUTRIENT CONTENT OF FERMENTATION BROILER LITTER USING DIFFERENT INOCULANS - E., Brahmana; Puspani, E.; Siti, N. W. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
This study aims to determine the nutritional content of fermented litter waste using different inoculants. The research was carried out at the Nutrition and Animal Feed Laboratory, Faculty of Animal Science, Udayana University from October to November 2021. The design used was a completely randomized design (CRD) consisting of four treatments, namely: litter as control (LF0), fermented litter EM-4 inoculant (LF1), yeast inoculant fermented litter (LF2), Bio-balitani fermented litter inoculant (LF3). Each treatment was repeated 4 times. The variables observed were dry matter (BK), organic matter (BO), crude protein (PK), crude fiber (SK), crude fat (LK), and ash content. The results showed that the use of inoculants significantly (P<0.05) increased crude protein content, crude fat, and ash content. The use of yeast inoculants (LF2) resulted in litters with the highest crude protein (P<0.05) and the lowest crude fiber (P<0.05). Based on the results of the study, it can be concluded that the use of inoculants in litter can increase the nutritional content, especially crude protein, crude fat, and ash, as well as reduce the crude fiber content. Key words: inoculum, EM4, yeast, Bio-balitani, litter, nutrient content.